Sistem Pakar Mendiagnosa Penyakit Kanker Usus Besar Pada Manusia Dengan Menerapkan Metode Hybrid Case Based - Rizky Delilah Rambe (STMIK Budi Darma, 2020)
Understanding of the expert system is a system that works like an expert in their field. A good expert system is designed to solve a particular problem by imitating the work of experts. With this expert system, ordinary people can solve problems that are quite complicated which actually can only be done by experts. For experts, this expert system will also help its activities as a very experienced assistant. Journal of the Hybrid Case Based method for expert systems is one method for building expert systems by making decisions on new cases based on solutions from previous cases. The concept of the case-based reasoning method was found from the idea of using documented experiences to solve new problems. The decision makers mostly use the experiences of previous problem solving to solve the problems faced now.